Perbedaan Antara Perendaman dalam Jus Mangga (Mangifera indica) dan Jus Jambu Biji Merah (Psidium guajava Linn) Terhadap Kekerasan Permukaan Email Gigi secara In Vitro - Deli Mona (Majalah Kedokteran Andalas, 2022)
Mango and guava juice has many nutrition for body health. Both of them have pH value less than 5,5 which can dissolve hidroxyapatite on enamel. The purpose of this study is to determine the difference of mango and guava juice immersion on enamel hardness surface. This study design is true experimental pretest and posttest. The study was performed on 32 samples were divided into 2 groups immersion into mango juice and guava juice. The samples was immersed for 25 hours. Enamel hardness surface measurements by Vickers Hardness Tester. The result of research show decreasing mean value of enamel hardness surface with pretest and posttest immersion on mango juice group is 125,62 VHN, immersion on guava juice group is 65,10 VHN. The result of paired T-test show the value  of p=0,000 for immersion on mango juice group and guava juice group. The result of independent T-test show there,s significant difference between immersion on mango juice and guava juice with the value of p=0,036. Conclusion of this research there was difference among enamel hardness surface pretest and posttest that immersed in mango and guava juice for 25 hours with the most decrease on mango juice immersed.